Radiation dosimetry of N-([(11)C]methyl)benperidol as determined by whole-body PET imaging of primates - Antenor-Dorsey, Jo Ann V. (2007)
PURPOSE: N-([(11)C]methyl)benperidol ([(11)C]NMB) can be used for positron emission tomography (PET) measurements of D(2)-like dopamine receptor binding in vivo. We report the absorbed radiation dosimetry of i.v.-administered (11)C-NMB, a critical step before applying this radioligand to imaging studies in humans. MATERIALS AND METHODS: Whole-body PET imaging with a CTI/Siemens ECAT 953B scanner was done in a male and a female baboon. After i.v. injection of 444–1221 MBq of (11)C-NMB, sequential images taken from the head to the pelvis were collected for 3 h. Volumes of interest (VOIs) were identified that entirely encompassed small organs (whole brain, striatum, eyes, and myocardium). Large organs (liver, lungs, kidneys, lower large intestine, and urinary bladder) were sampled by drawing representative regions within the organ volume. Time–activity curves for each VOI were extracted from the PET, and organ residence times were calculated by analytical integration of a multi-exponential fit of the time–activity curves. Human radiation doses were estimated using OLINDA/EXM 1.0 and the standard human model. RESULTS: Highest retention was observed in the blood and liver, each with total residence times of 1.5 min. The highest absorbed radiation doses were to the heart (10.5 mGy/kBq) and kidney (9.19 mGy/kBq), making these the critical organs for [(11)C]NMB. A heart absorption of 50 mGy would result from an injected dose of 4,762 MBq [(11)C]NMB. CONCLUSIONS: Thus, this study suggests that up to 4,762 MBq of [(11)C]NMB can be safely administered to human subjects for PET studies. Total body dose and effective dose for [(11)C] NMB are 2.82 mGy/kBq and 3.7 mSv/kBq, respectively.